Clinical and Analytical Performance of the BD Onclarity HPV Assay with SurePath Screening Samples from the Danish Cervical Screening Program Using the VALGENT Framework - Bonde, Jesper Hansen (J Clin Microbiol, 2020)
The Validation of HPV Genotyping Tests (VALGENT) framework is an international cooperation designed to evaluate human papillomavirus (HPV) assays with genotyping capabilities. Here, we assessed the performance of the BD Onclarity assay using Danish SurePath cervical screening samples collected under the fourth VALGENT installment, consisting of 998 consecutive samples from a screening population and 297 enriched samples with abnormal cytology (100 with atypical squamous cells of undetermined significance [ASCUS], 100 with low-grade squamous intraepithelial lesions [LSIL], and 97 with high-grade squamous intraepithelial lesions [HSIL]). The Onclarity assay detects six HPV genotypes individually (genotypes 16, 18, 31, 45, 51, and 52) and eight genotypes in three bulks (genotypes 33 and 58; genotypes 56, 59, and 66; and genotypes 35, 39, and 68). The clinical performance of the Onclarity assay for the detection of cervical intraepithelial neoplasia of grade 2 or worse (≥CIN2) and of two consecutive cytology outcomes negative for intraepithelial lesion or malignancy (2×NILM) was assessed relative to that of the GP5+/6+ PCR-enzyme immunoassay (GP-EIA) by a noninferiority test. The relative sensitivity for ≥CIN2 was 1.00 (95% confidence interval [CI], 0.97 to 1.04), and the relative specificity for 2×NILM was 1.04 (95% CI, 1.02 to 1.06). The Onclarity assay was found to be noninferior to the GP-EIA in terms of both sensitivity (P = 0.0006) and specificity (P < 0.0001). The type-specific performance of the Onclarity assay was also assessed, using the GP5+/6+ PCR with Luminex genotyping (GP-LMNX) as the comparator. The Onclarity assay showed good concordance for almost all HPV genotype groups. A stability analysis of SurePath samples was also performed, where a SurePath aliquot was stored refrigerated for 7 months and the internal control of the Onclarity assay was used as a marker for cellularity. The threshold cycle (C(T)) value was the same (24.8) in the first and second Onclarity runs, showing that a SurePath sample can be stored refrigerated for 7 months and still remain a valid test specimen.